2014
DOI: 10.1253/circj.cj-13-0346
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcome of a Single Stent Approach With and Without a Final Kissing Balloon Technique for Coronary Bifurcation

Abstract: 110YAMAWAKI M et al. Circulation JournalOfficial Journal of the Japanese Circulation Society http://www. j-circ.or.jp oronary bifurcation has been regarded as one of the most challenging lesion subsets due to poor clinical outcomes compared with non-bifurcated lesions. 1 Provisional intervention of the side branch (SB) after main vessel (MV) stenting is now the standard approach for most bifurcations. 2,3 Although the final kissing balloon technique (FKB) has been established as the first-line strategy for bif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 41 publications
(19 reference statements)
2
24
0
1
Order By: Relevance
“…Our computational findings are in keeping with the results because, in our considered models, although we simulated a relative tight residual stenosis in the LCX ostium after crossover technique, the distal LCX flow was not significantly affected. Regarding whether the final kissing balloon inflation should be performed after crossover stenting, our findings are in keeping with the results of clinical trials that documented that kissing inflation can be avoided in bifurcation lesions uneventfully treated with crossover technique [ 23 , 24 ]. Recent studies have demonstrated that a stent-induced increase in lumen diameter of the distal MV forces the position of the carina into the SB ostium and this carina shift is the main mechanism of the SB narrowing after MV stent implantation [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 85%
“…Our computational findings are in keeping with the results because, in our considered models, although we simulated a relative tight residual stenosis in the LCX ostium after crossover technique, the distal LCX flow was not significantly affected. Regarding whether the final kissing balloon inflation should be performed after crossover stenting, our findings are in keeping with the results of clinical trials that documented that kissing inflation can be avoided in bifurcation lesions uneventfully treated with crossover technique [ 23 , 24 ]. Recent studies have demonstrated that a stent-induced increase in lumen diameter of the distal MV forces the position of the carina into the SB ostium and this carina shift is the main mechanism of the SB narrowing after MV stent implantation [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 85%
“…Randomized trials comparing simple and complex techniques for non-left-main (LM) coronary bifurcation disease demonstrated that provisional one-stent is easier and not inferior to two-stent technique. [ 1 2 3 4 5 ] Although the provisional one-stent approach is now regarded as standard technique for most non-LM bifurcation lesions,[ 6 ] three studies reached inconsistent conclusions on necessity of final kissing ballooning (FKB) after main vessel stenting,[ 7 8 9 ] and there are no studies on FKB in LM bifurcation lesions. [ 10 11 12 13 14 15 16 17 18 19 20 ] So, whether FKB dilatation after one-stent implantation at LM bifurcation site remains unclear currently.…”
Section: Introductionmentioning
confidence: 99%
“…However, further studies showed that, despite using POT, C‐KBI in the provisional stenting strategy could not improve the angiographic or the clinical outcomes . This was mainly attributed to the geometric deformation of the MV stent and MV intimal injury, both of which might result in suboptimal MV outcomes …”
Section: Introductionmentioning
confidence: 99%